1998
DOI: 10.1076/apab.106.3.210.4377
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for a Possible Glycinergic Inhibitory Neurotransmission in the Midbrain and Rostral Pons of the Rat Studied by Gephyrin

Abstract: The data on the glycinergic transmission in the rostral brainstem are both few and controversial. The present report provides evidence for a possible glycinergic transmission in Sprague-Dawley rats, based on observations of immunocytochemical labeling for gephyrin, a 93 kDa protein and a component of the functional glycine receptor. A monoclonal antibody against gephyrin was used, and the reaction product was visualized by means of avidin-biotin-peroxidase procedure. The reaction product in midbrain and rostra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…The PPN is composed of a rich diversity of neuronal cell-types, with three major neurochemically distinct neuronal groups that have been identified in the PPN, namely cholinergic, GABA (gamma-aminobutyric acid)-ergic and glutamatergic neurons, which are heterogeneously distributed along its rostro-caudal axis (reviewer by Pienaar et al 2016). Glycine immunoreactivity was also reported to be present in the human PPN , as well as in various other vertebrate species (Fort et al 1993;Mineff et al 1998) neuropeptides. An example of this is somatostatin, to form part of somatostinergic brainstem neurons, which were shown to form afferent projections to the medial pre-optic nucleus, involved in regulating a variety of neuroendocrine processes, vegetative functions, sexual behavior, and for modulating the somatomotoris system (Giehl and Mestres 1995).…”
Section: Discussionmentioning
confidence: 99%
“…The PPN is composed of a rich diversity of neuronal cell-types, with three major neurochemically distinct neuronal groups that have been identified in the PPN, namely cholinergic, GABA (gamma-aminobutyric acid)-ergic and glutamatergic neurons, which are heterogeneously distributed along its rostro-caudal axis (reviewer by Pienaar et al 2016). Glycine immunoreactivity was also reported to be present in the human PPN , as well as in various other vertebrate species (Fort et al 1993;Mineff et al 1998) neuropeptides. An example of this is somatostatin, to form part of somatostinergic brainstem neurons, which were shown to form afferent projections to the medial pre-optic nucleus, involved in regulating a variety of neuroendocrine processes, vegetative functions, sexual behavior, and for modulating the somatomotoris system (Giehl and Mestres 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Although the cholinergic cell population of the PPN (Ch5) remains the best described cell group, this only accounts for *50 % of all neurons present in both the human and rat PPN (Mesulam et al 1983;Manaye et al 1999;Mena-Segovia et al 2009). Other non-cholinergic cell groups identified within the cholinergically defined border of the PPTg include glutamatergic (Clements and Grant 1990;Charara et al 1996), gamma-aminobutyric acid (GABA)ergic (Ford et al 1995;Jia et al 2003;Mena-Segovia et al 2009;Pienaar et al 2013) and glycinergic ones (Fort et al 1993;Mineff et al 1998;Pienaar et al 2013), while PPN neurons that co-express two or more neurotransmitters have also been described (Lavoie and Parent 1994;Jia et al 2003). Although the location of the Ch5 cholinergic population is traditionally used to delineate the boundaries of the PPN (Mesulam et al 1983;Mena-Segovia et al 2009;Pienaar and Van de Berg 2013), little is known regarding the other cell types and whether their cell bodies contribute to the PPN's boundary as clearly as the cholinergic neurons.…”
Section: Introductionmentioning
confidence: 99%
“…A number of studies have demonstrated that interdigitated with the Ch5 neurons is a population of smaller yet more numerous noncholinergic neurons (Rye et al ., 1988; Spann & Grofova, 1992; Lavoie & Parent, 1994; Honda & Semba, 1995; Takakusaki et al ., 1996; Steininger et al ., 1997). The exact neurochemical identity of these cells is still unknown, but a number of neurotransmitters including glutamate (Clements & Grant, 1990; Lavoie & Parent, 1994), GABA (Jones, 1991; Ford et al ., 1995; Charara et al ., 1996; Torterolo et al ., 2001), glycine (Mineff et al ., 1998) and galanin (Gai et al ., 1993) have been identified. Indeed, it is also known that the Ch5 neurons themselves contain other neurotransmitters, including glutamate (Bevan & Bolam, 1995) and most likely GABA (Pare et al ., 2003).…”
Section: Discussionmentioning
confidence: 99%